A novel F type plasmid encoding mcr-10 in a clinical Enterobacter ludwigii strain from a tertiary hospital in the Czech Republic - Sourenian, Tsolaire; Palkovicova, Jana; Papagiannitsis, Costas C; Dolejska, Monika; Hrabak, Jaroslav; Bitar, Ibrahim (Journal of global antimicrobial resistance, 2024)
OBJECTIVE: Here we describe a novel IncFIA plasmid harbouring mcr-10 gene in a clinical Enterobacter ludwigii strain isolated at the University Hospital in Pilsen in the Czech Republic. METHODS: The strain was subjected to antibiotic susceptibility testing. Whole genome sequencing was performed using Illumina for short-read sequencing and Oxford Nanopore Technologies for long-read sequencing followed by hybrid assembly. The resulting genome was used to detect species using average nucleotide identity, resistance genes, plasmid replicon and MLST (using centre for genomic epidemiology databases; ResFinder, PlasmidFinder and MLST, respectively) and virulence genes using VFDB. RESULTS: Τhe strain showed susceptibility against tetracycline, cefuroxime and chloramphenicol, and it was susceptible to the second and third generation of cephalosporins, carbapenems and colistin. Genome analysis identified the strain as E. ludwigii sequence type ST20 and located the mcr-10 gene on an IncFIA (HI1)/IncFII (Yp) plasmid (pI9455333_MCR10; 129 863 bp). Upon blasting the nucleotide sequence of pI9455333_MCR10 against the NCBI database, no similar plasmid sequence was detected, implying a novel plasmid structure. Nevertheless, it showed a partial similarity with pRHBSTW-00123_3 and FDAARGOS 1432, which were detected in Enterobacter cloacae complex (ECC) strains in wastewater samples in 2017 in UK and in 2021 in the United States, respectively, and pEC81-mcr, which was detected in a clinical Escherichia coli strain in 2020 in China. Moreover, I9455333cz genome carried virulence genes coding for curli fibers, fimbrial adherence determinants, siderophore aerobactin, iron uptake proteins and regulators of sigma factor. CONCLUSION: In conclusion, we identified a novel IncF plasmid harbouring mcr-10 gene in a clinical Enterobacter ludwigii strain. To our knowledge, this is the first clinical report of mcr-10 in the Czech Republic.
Keywords: Microbial Sensitivity Tests; centra terciární péče; enterobakteriální infekce; Enterobacter; Humans; mnohočetná bakteriální léková rezistence; Multilocus Sequence Typing; mikrobiální testy citlivosti; Whole Genome Sequencing; Colistin; lidé; Enterobacteriaceae Infections; plazmidy; antibakteriální látky; bakteriální proteiny; Drug Resistance, Multiple, Bacterial; sekvenování celého genomu; mcr-10; Anti-Bacterial Agents; Enterobacter ludwigii; multilokusová sekvenční typizace; Enterobacter cloacae complex; Czech Republic; Bacterial Proteins; Tertiary Care Centers; Česká republika; Plasmids